Piping materials : selection and applications - Smith, Peter, 1951 June 7- (Elsevier, 2005)
The only book of its kind on the market, this book is the companion to our Valve Selection Handbook, by the same author. Together, these two books form the most comprehensive work on piping and valves ever written for the process industries. This book covers the entire piping process, including the selection of piping materials according to the job, the application of the materials and fitting, trouble-shooting techniques for corrosion control, inspections for OSHA regulations, and even the warehousing, distributing, and ordering of materials. There are books on materials, fitting, OSHA regulations, and so on, but this is the only "one stop shopping" source for the piping engineer on piping materials. - Provides a "one stop shopping" source for the piping engineer on piping materials - Covers the entire piping process. - Designed as an easy-to-access guide